Organoleptic Testing Of Broiler Chicken Meat Quality With The Addition Of Corn Leaf Flour and Seaweed - Taufik Daud; Ellen J. Saleh; Sry Yenny Pateda (International Journal of Technology and Education Research, 2025)
The addition of corn leaf and seaweed powder will have a positive effect on broiler meat quality in terms of consumer acceptance based on organoleptic testing. This study aims to determine the effect of adding corn leaf flour and seaweed on the quality of broiler chickens. The research design used a completely randomized design (CRD) with 6 treatments and 3 replicates, with the administration of commercial feed (control), corn leaf flour (5-15%), and seaweed flour (5-15%). The variables observed in the study were organoleptic properties (color, aroma, texture) using 30 untrained panelists. The data obtained from the organoleptic test results were analyzed using Analysis of Variation (ANOVA). The results of the ANOVA statistical analysis showed that feeding a mixture of corn leaf flour and seaweed did not have a significant effect (P<0.05). The average organoleptic test results for color were 6.8 (somewhat appealing), aroma 6.9 (somewhat appealing), and texture 7.9 (quite appealing). The conclusion that can be drawn from this study is that adding corn flour and seaweed does not significantly affect the panelists' preference for broiler chicken meat and can reduce the sensory quality or consumer acceptance of broiler chicken